1166 All of us at risk? how to access the hazardousness of electromagnetic fields. (24th April 2018) - Neumann, Claudine; Wittlich, Marc
Abstract : Introduction: Electromagnetic fields (EMF) are everywhere. Most of our technology today and in future is based upon applications using electric currents, magnets and thus bear the risk to emit hazardous levels of electromagnetic fields. For this purpose workplace exposure due to EMF has to be assessed to ensure that impermissible exposure of employees is avoided. Particular attention has to be paid to employees with medical implants. Our presentation focusses on the process of exposure assessment of electromagnetic fields at several industrial workplaces. Methods: Commonly measurements are performed to assess electromagnetic fields at workplace. Electromagnetic field simulations via numerical calculations can be needful if the EMF source is very complex or direct measurement is not possible. Measurements require a high degree of expert knowledge to assess the entire exposure scenario: relevant field sources have to be identified with both knowledge of fundamental functionality and operating frequency. Risk assessment usually considers working procedures and the whole working area at large. Results: Several industrial applications imply a potential risk for safety and health of employees at their workplace. Thus, exposure has to be minimised by either technical, organisational and/or personal measures. Most of the required measures are simple as well as inexpensive, e.g. provision of operating instructions, safety instructions of employees, labelling of critical areas or just increase of distance to the field source. Only few cases require extensive measures, which may lead to a prohibition to resume work – especially for employees with active implants. Discussion: EMF at workplace are underestimated and somehow neglected in the scope of risk assessment. That's why people have to become sensitised to this topic to recognise possible hazards. Especially employees with medical implants are particularly vulnerable with regard to EMF. For this purpose a specially tailored risk assessment procedure is needed to address this problem completely and more adequate.